Portal pengguna berpandukan konsep CRM kajian kes: Bahagian Penguatkuasa KPDN & HEP, Johor Bahru - Ham, Kau Fei (2006)
Consumer portal application with CRM concept practices is one of an instance of internet services technology advancement, which orientates on consumer society centric, such as information requirements, consumer needs, and their behaviors. Applying CRM concepts in a consumer portal are intend for delivering more efficiency consumer services and consolidating long-term consumer society relationship with enforcement division. Due to massive challenges that are confronted by enforcement division in the way of managing consumer affairs and domestic trade in Johor Bahru even to smooth over the procedural of consumer society management relationship, its necessary for developing portal system as a provider, preserver, and disseminator agent to display current information with the supporting of dynamic database system. Otherwise, adoption of proposed conceptualization like customer relationship management process and cross-functional CRM approach in a web portal application that will be given highly prediction of reaching consumer satisfaction and optimum their values. During this project development process, methodology of information technology management, which based on PMBOKÂ® Guide (2000) has been choosen as a crucial reference, nevertheless methodology of system development is rely on phased development model with an eye to assure client-server architecture design for a consumer portal shall be able to achieve interactive, simple, and well proper order of web services. The result shows that the consumer commmunities feeling comfortable to deploy this kinds of portal system in the area of e-services.